“Female courage” in prison literature in Malaysia and the Philippines - Abdul Manaf, Nor Faridah; Jaafar, Farizah; Ismail, Khamsiah; Hashim, Che Noraini (International Society of Communication and Development Between Universities (ISCOBU), 2016)
Purpose: This study examines selected prison literary writings by women prisoners in Malaysia and the Philippines on “female courage” as a means to protect them against abuse.Design: This study uses qualitative approach in which content analysis of selected writings by women prisoners in Malaysia and the Philippines as well as examining literature reviews on gender and psychology of courage to help understand the use of courage in safeguarding female body and female integrity. Methods: Eight short narratives by women prisoners in Malaysia and the Philippines are analysed based on how they or their female protagonists assert their courage as a way to protect themselves against abuse. Where available, selected women prison writers are interviewed to explain further their coping mechanism and also how writing creatively has helped them remain strong and positive while waiting for their release. Findings: Findings on impact of gender and psychology of courage in prison women’s writing will help affirm that courage in women is necessary and can be taught. This will help other women to cope in the face of abuse. Conclusion: There is a need to relook at ways to instil courage in women prisoners so that their mental health is well-taken of.